LncRNA‐GAS5 related to the processes of recurrent pregnancy loss by regulating Th1/Th2 balance - Miao‐Miao Wang; Ji‐Xiang Zhong; Yuan‐Yuan Xiang (Kaohsiung Journal of Medical Sciences, 2021)
Abstract Recurrent pregnancy loss (RPL) is defined as three or more consecutive spontaneous loss of pregnancy and the reason of 50% RPL is unknown. GAS5 is a long non‐coding RNA, which has been found to be an immune responses regulator and to be relate to autoimmune diseases. However, the roles of GAS5 during the pathophysiological processes of RPL is unclear. In the present study, the levels of GAS5 were examined in the plasma and trophoblasts from 30 patients with RPL and 15 healthy controls. GAS5 was found overexpressed in patients with RPL and positively correlated with the protein levels of TNF‐α in the plasma and trophoblasts. Predicted by bioinformatics tools and confirmed by luciferase assay, GAS5 was identified to function as a competing endogenous RNA (ceRNA) binding with miR‐140‐5p and protects TNF‐α expression in HTR‐8/SVneo cells and primary trophoblasts. Activated Naïve T cells co‐cultured with the medium from GAS5 overexpression HTR‐8/SVneo cells or primary trophoblasts exhibited Th1 bias by expression more IFN‐γ, TNF‐α and less IL‐4, IL‐10. In conclusion, GAS5 was overexpressed in the plasma and trophoblasts from RPL patients, which contributes to Th1 bias by binding with miR‐140‐5p.